Investigation of the fiber Bragg grating inscribed in multimode fiber by femtosecond laser. Issue 1 (January 2017) - Jiang, Yajun; Yang, Dexing; Yuan, Yuan; Xu, Jian; Li, Dong; Wang, Meirong; Zhao, Jianlin
ABSTRACT: Multimode fiber Bragg grating (MFBG) is inscribed in graded‐index multimode fiber using infrared femtosecond laser and phase mask. Multiple dips are observed in the transmission spectrum of MFBG. There is not only self‐coupling effect between the forward and backward principal modes, but also the mutual coupling effect between the neighbor modes. The induced refractive index modulation of 6.4 × 10 −4 is achieved for a peak power density of 4.1 × 10 13 W/cm 2 without any fiber sensitization. Thermal experiment results show that the MFBG belongs to type I grating. The transmission spectrum of MFBG shifts linearly with the strain and pressure at sensitivities of 1.27 ± 0.002 pm/με and −3.3 ± 0.06 pm/MPa, respectively. The MFBGs are expected to be used for multichannel filters, multiwavelength fiber lasers, and multiparameter sensing. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:214–219, 2017